Sound in the real world - Milios, Rita (Minneapolis, MN : ABDO Pub., 2013)
Describes the properties of sound, its study by scientists, and the use of sound technology, and discusses sound in both the human and animal worlds.
Includes bibliographical references (p. 47) and index.
Keywords: Sound -- Juvenile literature; Sound; Sound